Designing Halal Food Security Framework: Maqasid Shariah Compliance Perspective in Malaysia - Abdul Manap, Nur Marina; Zainal, Zalina; Mohammad Bahar, Nor Fadzlin; Md. Tahir, Raziah (UUM, 2022)
Halal ecosystems create a favorable setting for long-term halal food security because halal is the gold standard for product quality and safety. This study intends to create a new halal food security framework, investigate the influence of halal development on food security, and determine the number of halal certificates that impact food security sustainability. This research has employed Vector Error Correction Model (VECM) technique and Threshold analysis. The findings showed that by incorporating halal development factors and incorporating interaction between halal development and food production, halal development successfully increases food security sustainability. Furthermore, increasing the number of company foods and beverages that receive Halal Certificates will aid Malaysia in improving and maintaining food security.